2017
DOI: 10.26582/k.49.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological aspects of sports injuries among male professional soccer players in Croatia

Abstract: Abstract:The aim of this study was to assess occurrence of sports injuries among professional male soccer players in relation to their psychological characteristics. This prospective cohort study was conducted during the 2013/2014 sports season among all professional players with the first team contract in the first Croatian soccer league. A stratified sample of 182 male soccer players were selected for the assessment. They were surveyed during their preparation period before the beginning of the season and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…There are also numerous studies which cite the incidence and prevalence of sports injuries in the context of organised sport and their relationship with some psychological attributes of players [ 4 , 6 7 ]. Madzar et al [ 8 ] and Zurita-Ortega et al [ 9 ] have identified a relationship between injury occurrence and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…There are also numerous studies which cite the incidence and prevalence of sports injuries in the context of organised sport and their relationship with some psychological attributes of players [ 4 , 6 7 ]. Madzar et al [ 8 ] and Zurita-Ortega et al [ 9 ] have identified a relationship between injury occurrence and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…According to the earlier research findings carried out by S. Laborde, F. Dosseville, and M.S. Allen [1]; Madzar T. et al [36]; Znazen H. et al [37], elite players (professional athletes) apply different types of mental skills in order to control their competitive anxiety; they have higher selfconfidence and positive effect on emotions regulation. Second, a subject of previous researches consists of both male and female athletes.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, indicaram uma predição que sustenta a hipótese de que jogadores de futebol profissional que sofreram lesões musculoesqueléticas severas provavelmente desenvolverão sintomas subsequentes de transtornos mentais comuns (Kiliç et al, 2018). Um estudo avaliando a ocorrência de lesões em relação às características psicológicas, sugeriu que a probabilidade de lesão é principalmente influenciada por comportamentos impulsivos e pelos altos escores em uma escala de ansiedade (Madžar, Milošević, Hrabač & Heningsberg, 2017); outro estudo visou determinar o risco de fraturas, entre elas as que ocorrem por estresse, em um time de futebol, tendo apresentado estimativas de que um time pode apresentar 1 a 2 fraturas por temporada. Há mais fraturas traumáticas do que fraturas por estresse, entretanto as fraturas por estresse geram ausências mais longas (Larsson, Ekstrand & Karlsson, 2013).…”
Section: Critérios De Seleçãounclassified
“…Tais evidências denotam a demanda de clubes e confederações ofertarem serviços direcionados à gestão do estresse e da ansiedade, para que estes se estabeleçam em níveis adequados à saúde física e mental dos jogadores (Aughey et al, 2016;Tharawadeepimuk & Wongsawat, 2017). Um destes estudos indicou inclusive que a probabilidade de um atleta se lesionar pode ser influenciada pelos níveis de ansiedade e estresse (Madžar et al, 2017).…”
Section: Umaunclassified